Examining antibiotic use in Kenya: farmers’ knowledge and practices in addressing antibiotic resistance - Harrison Rware; Kansiime K. Monica; Mugambi Idah; Makale Fernadis; Ikiror Davis; Wako Buke; Danielsen Solveig; Karanja Daniel; Chacha Duncan; Byskov Morten; Hyams Keith (CABI Agriculture and Bioscience)
Abstract Background Antibiotics hold the promise of mitigating the spread of livestock diseases while enhancing productivity. However, there is global concerns surrounding the improper handling and administration of antibiotics, which has led to an alarming rise in antimicrobial resistance (AMR). Kenya is currently listed as an AMR hotspot. This study assesses farmers’ knowledge and practices on antibiotics in livestock production, knowledge on AMR as well as factors influencing farmers’ knowledge of antibiotic safety and resistance, and antibiotics use. Methods A across-sectional, quantitative survey was employed with 319 farming households in five counties in Kenya. Multivariate regression analysis was used to identify explanatory factors. Results About 80% of households use antibiotics in their livestock, and 58% administer the antibiotics themselves. The vast majority of farmers buy antibiotics without a prescription. Antibiotics are used for both therapeutic and non-therapeutic purposes, the latter mainly in form of growth promoters and feed enhancers in poultry. The withdrawal periods reported by farmers are shorter than the officially recommended periods. Although the majority of farmers reported risky antibiotic practices, most (76%) were well aware of bacterial AMR. Nineteen of 21 knowledge statements on AMR and safe use of antibiotics were answered correctly by 55–89% of respondents, indicating considerable farmer knowledge on different aspects of antibiotics risk, while certain knowledge gaps remain. Number of livestock owned was the factor most positively influencing farmers’ knowledge on AMR and safe use. Conclusion Kenya has made notable progress towards creating knowledge and awareness of farming communities on the risks and requirements associated with antibiotic use in livestock. Nonetheless, farmers’ antibiotics practices continue to constitute considerable risk of further AMR development. This shows that knowledge is not enough to ensure fundamental behavioral change. There needs to be an enabling environment driven by (1) effective policy interventions and enforcement to ensure compliance with set guidelines for antibiotic use; (2) research on and deployment of alternatives, such as probiotics, vaccinations and disease prevention measures, (3) continued public awareness raising and education using multiple channels to reach farmers and, (4) strengthened cross-sector, multi-stakeholder collaboration to address the multi-dimensional complexities of AMR.